Analisis Perbedaan Kadar Nikel Antara Front Penambangan dan Stockpile Pada PT Rockstone Multi Mining Indonesia: Analysis of the difference in Nickel Grade Between the Mining Front and Stockpile at PT Rockstone Multi Mining Indonesia - Maulana, Wahyu; Chalik, Citra Aulian; Thamsi, Alam Budiman (Journal of Engineering Science and Technology Applications, 2024)
PT Rockstone Multi Mining Indonesia Central Sulawesi is one of the companies that manages laterite nickel ore into ferronickel (FeNi) products. This study aims to determine the percentage of nickel content found in the mining front to the stockpile and to find out what percentage of the change in nickel content from the mining front to the stockpile and analyze the factors of the change in the level from the mining front to the stockpile. This study uses the field observation method. In the mining front data , with a total of 17 domes, the average level of Ni Front of reclamation is 1.91 while the average level of Ni stockpile is 1.90. When summing up the average value of the mining front and stockpile levels , a decrease in nickel content of 0.01% was obtained. The factors that cause changes in nickel levels are waterlogging, dredging of the Stockpile floor, the use of used sacks for samples, unclean buckets, unclean dump truck tubs, sampling errors, and preparation errors.